1997
DOI: 10.1055/s-0038-1656114
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte Rheological Properties Are Altered in Patients with Diffuse Atherosclerosis

Abstract: SummaryTo evaluate whether atherosclerosis may be associated with altered leucocyte rheology, we assessed leucocyte count (by Coulter counter), aggregation (by means of the leukergy test) and expression of adhesion molecules integrin LFA-1 and CD 44 (by means of immunofluorescence staining and flow cytometry) in 9 patients with carotid plus lower limb artery atherosclerosis (group A), 14 patients with carotid atherosclerosis only (group B) and 23 controls without atherosclerosis (group C). The level of LFA-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In various earlier studies it has been shown to correlate with disease activity during infections [1^3], rheumatic diseases [4^5], ischaemic heart diseases [6^8], brain conditions [9^13], in£ammatory bowel diseases [14^16], as well as trauma-related in£ammatory responses [17,18] and atherosclerosis [19]. This test is based on the observation that white blood cells increase their adhesiveness following in£am-matory stimuli [20].…”
Section: Introductionmentioning
confidence: 99%
“…In various earlier studies it has been shown to correlate with disease activity during infections [1^3], rheumatic diseases [4^5], ischaemic heart diseases [6^8], brain conditions [9^13], in£ammatory bowel diseases [14^16], as well as trauma-related in£ammatory responses [17,18] and atherosclerosis [19]. This test is based on the observation that white blood cells increase their adhesiveness following in£am-matory stimuli [20].…”
Section: Introductionmentioning
confidence: 99%
“…The observation that bacterial infections increase leukocyte adhesiveness is not new [4,5,11]; increased adhesiveness/aggregation is nonspecific and can be observed in other inflammatory conditions, including arthritis [12], inflammatory bowel diseases [13], trauma [14], myocardial infarction [15], stroke [16] and atherosclerosis [17]. However, viral infections differ from bacterial and noninfectious inflammatory conditions by the absence of increased leukocyte adhesiveness/aggregation both in peripheral blood [9] and in CSF [18].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation confers increased adhesive properties upon white blood cells (WBC) [1].We [2][3][4][5][6] and others [7][8][9][10][11][12][13] have used a simple slide test to reveal the increased state of leukocyte adhesiveness/aggregation (LAA) in the peripheral blood of individuals during various conditions of infection /inflammation.The leukocyte adhesiveness/aggregation test (LAAT) was shown to be a useful laboratory test to detect the presence [14,15] and severity [4,5,[16][17][18] of an inflammatory response. We have recently introduced the novel technology of image analysis to detect the presence of WBC in the peripheral blood slides as well as for the quantitation of their degree of adhesiveness/aggregation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%